Relationships between milk fatty acids composition in early lactation and subsequent reproductive performance in Czech Fleckvieh cows - Stádník, L; Ducháček, J; Beran, J; Toušová, R; Ptáček, M (Animal reproduction science, 2015)
Increase of milk yield after calving causes changes in milk fatty acids (FA) composition and simultaneously corresponds with reproduction performance decrease. The objective of this study was to evaluate the relationships between milk FA group composition (SFA, saturated fatty acids; MUFA, monounsaturated fatty acids; and PUFA, polyunsaturated fatty acids) during the first 5 lactation weeks and subsequent reproductive results (INT, calving to first service interval; NUM, number of services per conception, and DO, days open) in Czech Fleckvieh cows. A total of 1231 individual milk samples from 382 cows were collected and subsequently analyzed. Simultaneously, body condition score (BCS) was weekly evaluated as well. Software SAS 9.1 was used for statistical analysis. Daily milk yields increased whereas BCS, milk fat and protein contents decreased during period observed. The reduction of basic milk components (% of fat, % of protein) was associated with increased SFA and decreased MUFA, respectively PUFA contents. Significant (P<0.01-0.05 days) increase in NUM (+0.15 to +0.29 AI dose) and DO (+8.16 to 15.44 days) were detected in cows with the lowest SFA content. On the contrary, cows with the highest content of MUFA presented significantly (P<0.01-0.05) higher values of NUM (+0.13 to +0.30) and DO (+7.26 to +15.35 days). Milk FA groups composition in early lactation potentially used as NEB indicators, especially SFA and MUFA proportion, affected subsequent reproductive results of Czech Fleckvieh cows. Therefore, its post-partum values could serve as predictors of potential fertility of dairy cows.
Keywords: Fatty acids; Cattle; Animals; Milk composition; skot; Negative energy balance; Female; Fatty Acids, Monounsaturated; ženské pohlaví; Reproduction; laktace; fertilita; Fatty Acids, Unsaturated; Milk; Fertility; nenasycené mastné kyseliny; kyseliny mastné mononenasycené; zvířata; mléko; Lactation